1989
DOI: 10.1164/ajrccm/140.3.634
|View full text |Cite
|
Sign up to set email alerts
|

Viral Etiology in Acute Lower Respiratory Infections in Children from a Closed Community

Abstract: The aim of this study was to determine the viral agents associated with acute lower respiratory infections (ALRI) in young children. During a 2-yr period, 204 nasopharyngeal aspirates (NPA) from children under 4 yr of age living in an orphanage and exhibiting febrile ALRI were studied by both indirect immunofluorescence (IIF) and isolation in four cell lines. NPA cell smears as well as tissue culture cells exhibiting cytopathic effect (CPE) or hemadsorption were stained by IIF for respiratory syncytial virus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 2 publications
0
29
0
2
Order By: Relevance
“…RSV is the main cause of childhood viral ARI [28] and has been detected among other respiratory viruses, mainly influenza A, rhinovirus, coronaviruses and parainfluenza viruses, in exacerbations of COPD [29][30][31][32]. For older adults it has been shown that the diagnosis of RSV with less sensitive tests can be difficult and are not always reliable, leading to the complementary use of different methods for RSV detection [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…RSV is the main cause of childhood viral ARI [28] and has been detected among other respiratory viruses, mainly influenza A, rhinovirus, coronaviruses and parainfluenza viruses, in exacerbations of COPD [29][30][31][32]. For older adults it has been shown that the diagnosis of RSV with less sensitive tests can be difficult and are not always reliable, leading to the complementary use of different methods for RSV detection [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The adenovirus species C serotypes (Ad1, Ad2, Ad5, and Ad6) are commonly associated with upper and lower respiratory tract infections in children less than 5 years of age (1,6,9). These viruses are only weakly pathogenic in normal hosts, where the rate of asymptomatic primary infection ranges from 50 to 90% (2,6,9).…”
mentioning
confidence: 99%
“…The common, endemic species C adenoviruses (serotypes 1, 2, 5, and 6) normally cause respiratory tract infections in young children (Brandt et al, 1969;Avila et al, 1989) and persistent infection of lymphoid tissues (Garnett et al, 2002). We investigated whether adenovirus infections could be correlated with ALL by studying Guthrie cards from children who later developed ALL and healthy controls.…”
mentioning
confidence: 99%